Scientific and regulatory progress in advancing paediatric oncology drug development in the EU and in the US - Reggiardo, Giorgio; Natale, Alessandra; Santoro, Nicola; Giannuzzi, Viviana; Pansieri, Claudia; Felisi, Mariagrazia; Bonifazi, Donato; Ceci, Adriana (Frontiers in Medicine, 2025)
IntroductionThis study provides an updated overview of progress in paediatric oncology, following legislative and regulatory initiatives in the European Union (EU) and in the United States (US). In particular, the US Research to Accelerate Cures and Equity (RACE) Act 2017 mandated new paediatric indications based on drug Mechanism of Action (MoA), and the EE 2015 revision of the waivers system allowed more agreed Paediatric Investigation Plans (PIPs).Materials and methodsThe sample included: (a) products with paediatric oncology marketing authorisation in the US and in the EU from 2007 to 2024; (b) PIPs granted in the EU during the same period. Linear regression models were used to evaluate the time-trends in approvals, and the chi-squared test was applied to compare categorical variables in the periods ranging between 2007–2017 and 2018–2024.ResultsIn the 2018–2024 period, more paediatric products have been approved in both regions, with the US progressing at a rapid pace. The approved indications for solid tumours (STs) are growing, with innovations from targeted and immunotherapeutic agents prevailing over chemotherapies. The approval of PIPs reflects a similar trend to that of the products. Both paediatric products and PIPs are granted mainly to address specific childhood tumours, rather than those derived solely from adult indications. However, several unmet needs remain to be addressed.DiscussionBoth regions are working to advance paediatric oncology medicines. However, a significant gap still exists between the EU and the US, with the EU lagging behind. This discrepancy should be a priority for Europe. It is unlikely that abolishing the Paediatric Regulation, proposed as part of the Pharmaceutical Legislation reform, in the absence of other initiatives and substantial investments, would be the right solution.